2010
DOI: 10.1111/j.1198-743x.2010.03296.x
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific long-term mortality rates in patients recovered from community-acquired pneumonia compared with the general Dutch population

Abstract: Insights into long-term mortality, especially into the cause of death after initial recovery from an episode of community-acquired pneumonia (CAP), may help in determining optimal preventive measures in such patients. Prospective observational cohort studies were conducted to compare cause-specific long-term mortality rates for 356 patients who had recovered from CAP with those of the general Dutch population (16.3 million) between 2003 and 2007. The Dutch Municipal Public Records Database and death certificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…Another study by KAPLAN et al [6] of 158,960 Medicare patients with community-acquired pneumonia who were matched to 794,333 patients hospitalised for other conditions demonstrated a 1-yr mortality of 40.9% for the pneumonia group versus 24.9% for the controls. Several other studies support the concept that there is markedly increased mortality for up to several years afterwards for those that initially survive an episode of pneumonia [7][8][9][10][11][12].…”
mentioning
confidence: 69%
“…Another study by KAPLAN et al [6] of 158,960 Medicare patients with community-acquired pneumonia who were matched to 794,333 patients hospitalised for other conditions demonstrated a 1-yr mortality of 40.9% for the pneumonia group versus 24.9% for the controls. Several other studies support the concept that there is markedly increased mortality for up to several years afterwards for those that initially survive an episode of pneumonia [7][8][9][10][11][12].…”
mentioning
confidence: 69%
“…Thirdly, most studies have evaluated 30-day pneumonia mortality as the primary endpoint. Recent studies showed that a clinically important number of subjects with pneumonia have a cardiovascular event within 90 days of hospital admission [44,45]. It is conceivable that the observed benefits of statins do not represent anti-inflammatory effects during the acute phase of pneumonia, but are mainly the result of a lack of statin treatment being associated with cardiovascular death after pneumonia.…”
Section: Statinsmentioning
confidence: 99%
“…Streptococcus pneumoniae (the pneumococcus) is the most frequent cause of CAP, bacteremia, and sepsis (18). Pneumococcal infection is associated with greater disease severity and increased risk of death compared with other causes of pneumonia; in one study, the mortality risk was almost threefold higher (19). Infection with S. pneumoniae has also been directly associated with adverse cardiac events.…”
mentioning
confidence: 99%
“…Infection with S. pneumoniae has also been directly associated with adverse cardiac events. In a 2007 study by Musher and colleagues (20), 19.4% of 170 admitted adult patients experienced some form of an adverse cardiac event; most importantly, those who experienced an adverse cardiac event during pneumonia were at significantly higher risk for death than those with pneumococcal pneumonia alone. Herein, we review the pathogenic mechanisms by which S. pneumoniae directly inhibits cardiac contractility.…”
mentioning
confidence: 99%